The agrarian economy of Oman (132-280/749-893) in Arabic sources - Ubaydli, Ahmad (Journal of Islamic Studies, 1993)
Conclusion (p. 48): the agrarian system which existed in Oman in the period under consideration (the first Ibāḍī state, 132-280/749-893), together with fishing and pearling and maritime trade, enabled the country to establish a base for economic self-reliance. This was manifested in a tendency to resist central authority. The Aflāj irrigation system in its Omani context made it possible for its users to be more independent and to have more influence over the local authorities. Ibāḍism seems to have reflected these two tendencies well enough for the Omanis to adopt it. Both classical Arabic and Omani sources reflect this situation and, taken together, provide a detailed description which illuminates various aspects of the agrarian economy that existed in Oman during this period.
Keywords: Agriculture -- Oman